2006
DOI: 10.1677/jme.1.01962
|View full text |Cite
|
Sign up to set email alerts
|

GATA-4 is a granulosa cell factor employed in inhibin-α activation by the TGF-β pathway

Abstract: Part of heterodimeric inhibin, inhibin-is crucial for mammalian ovarian function. Regulation of inhibin-expression in granulosa cells is both endocrine, primarily by follicle-stimulating hormone (FSH), and paracrine, primarily by members of the transforming growth factor (TGF-) superfamily. Smad proteins transmit TGF-signals to the nucleus, but the cooperating transcription factors involved in inhibin-promoter activation remain unknown. Transcription factor GATA-4 regulates inhibin-in gonadal cells, and the FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 61 publications
3
36
0
Order By: Relevance
“…We focused on TGF-b as GATA4 induced p15Ink4b, known to be regulated by TGF-b, including in astrocytes (Hannon and Beach, 1994;Quelle et al, 1995) (Rich et al, 1999). We found TGF-b stimulation induced GATA4 expression in astrocytes, a result which was also supported by studies in regulation of gastrointestinal differentiation genes (Afouda et al, 2005;Anttonen et al, 2006;Belaguli et al, 2007). Furthermore, our results showed that GATA4 knockdown inhibited TGF-b and p15Ink4b-mediated growth suppression in the astrocytes.…”
Section: Discussionsupporting
confidence: 75%
“…We focused on TGF-b as GATA4 induced p15Ink4b, known to be regulated by TGF-b, including in astrocytes (Hannon and Beach, 1994;Quelle et al, 1995) (Rich et al, 1999). We found TGF-b stimulation induced GATA4 expression in astrocytes, a result which was also supported by studies in regulation of gastrointestinal differentiation genes (Afouda et al, 2005;Anttonen et al, 2006;Belaguli et al, 2007). Furthermore, our results showed that GATA4 knockdown inhibited TGF-b and p15Ink4b-mediated growth suppression in the astrocytes.…”
Section: Discussionsupporting
confidence: 75%
“…Also, TGFb1 increased the expression of transcription factor GATA4 in a granulosa tumor cell line KK1 (Anttonen et al 2006), and GATA4 has recently been reported to bind and stimulate FSH receptor promoter activity in mouse granulosa cells (Bennett et al 2012).…”
Section: Fs Hrmentioning
confidence: 95%
“…Of interest, GATA-4 has recently been shown to cooperate with Smad3 to mediate TGFβ signalling in the regulation of inhibin α. (Anttonen et al 2006). Thus, TGFβ, Smad3…”
Section: Transgenic (Tg) Murine Models For Adrenocortical Tumorigenesismentioning
confidence: 95%